2010
DOI: 10.1111/j.1600-0854.2010.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Density of the Glutamate Transporter EAAC1 is Controlled by Interactions with PDZK1 and AP2 Adaptor Complexes

Abstract: † These authors contributed equally to the study.The glutamate transporter excitatory amino acid carrier (EAAC1/EAAT3) mediates the absorption of dicarboxylic amino acids in epithelial cells as well as the uptake of glutamate from the synaptic cleft. Its cell-surface density is regulated by interaction with accessory proteins which remain to be identified. We detected a consensus sequence for interaction with post-synaptic density- 95/Discs large/Zonula occludens (PDZ) proteins (-SQF) and a tyrosine-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 52 publications
(79 reference statements)
3
37
0
Order By: Relevance
“…Such a mechanism, based on stabilization by PDZ-ligand interaction and AP-2-mediated endocytosis, has so far only been described for a few proteins, such as the NR2B subunit of the neuronal NMDA receptor (Prybylowski et al, 2005) and the glutamate transporter excitatory amino acid carrier 1 (EAAC1) in MDCK cells. In the latter case, AP-2 and the PDZ domain of PDZK1 antagonistically regulate surface levels of EEAC1 by binding to two closely adjacent binding sites in EEAC1 (D'Amico et al, 2010). Currently, we can only speculate about the mechanisms that might determine which of the binding partners -AP-2 or Sdt -binds to Crb.…”
Section: Discussionmentioning
confidence: 99%
“…Such a mechanism, based on stabilization by PDZ-ligand interaction and AP-2-mediated endocytosis, has so far only been described for a few proteins, such as the NR2B subunit of the neuronal NMDA receptor (Prybylowski et al, 2005) and the glutamate transporter excitatory amino acid carrier 1 (EAAC1) in MDCK cells. In the latter case, AP-2 and the PDZ domain of PDZK1 antagonistically regulate surface levels of EEAC1 by binding to two closely adjacent binding sites in EEAC1 (D'Amico et al, 2010). Currently, we can only speculate about the mechanisms that might determine which of the binding partners -AP-2 or Sdt -binds to Crb.…”
Section: Discussionmentioning
confidence: 99%
“…GLAST and GLT1 (Chaudhry et al 1995) as well as the neuronal transporter EAAT4 (Tanaka et al 1997;Dehnes et al 1998) are almost exclusively found in the plasma membrane. Cell culture studies indicate that EAAC1 trafficking to the plasma membrane is regulated by various signaling pathways (Davis et al 1998;Guillet et al 2005;Sheldon et al 2006;d'Amico et al 2010). This may suggest that intracellular EAAC1 transporters serve as a reserve pool that can be recruited to cell surface under specific physiological conditions.…”
Section: Eaac1 Expressed In Nst Dendrites Is Mainly Intracellularmentioning
confidence: 98%
“…This observation is unlikely to be an artifact, because Shashidharan et al (1997) observed a similar localization of EAAC1 using a different antibody (see above) and because EAAC1 was readily detected in the brush border in the kidney. Furthermore, cell culture studies indicate that only 20 -30% of EAAC1 is localized at the plasma membrane (Fournier et al, 2004;Sheldon et al, 2006), and can be inserted into the plasma membrane in response to activity (González et al, 2007;D'Amico et al, 2010;Ross et al, 2011).…”
Section: Is Eaac1 Present In Nerve Terminals?mentioning
confidence: 99%